Liuqin Drama’s Origin and Early Development - Zhibo Wang (European Scientific Journal, ESJ, 2016)
Liuqin Drama did not have a long history. It started from Qing Dynasty. It did not have a glorious background. It actually started from begging. Yet its singing is marvelous. Its early name was “Lahun” Tune, which literally meant “soul-pulling” Tune in Chinese. Its attraction is enormous, and with generations of accumulation of artistic culture, it has become one of the major genres of folk drama of Southern Shandong, Northern Jiangsu and Northeastern Anhui Province. This paper introduces the beginning and the later development of the Liuqin Drama.